2013
DOI: 10.1111/eth.12052
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Behavioural Categories and Social Influences in the Gregarious Big Brown Bat (Eptesicus fuscus)

Abstract: Behavioural plasticity is a critical component of natural selection leading to evolution. However, a surge of studies in the last two decades has discovered a distinct limit to behavioural plasticity, commonly referred to as behaviour types and behavioural syndromes. We set out to understand the relationships across behavioural categories in wild‐caught adult, female big brown bats and how they compare between social and solitary behaviours. Using bats sampled from four different maternity colonies, we ran a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The Spix's disc-winged bat (Thyroptera tricolor) within social groups exhibits consistent individual differences in vocal behavior [38,39]. The isolated behaviors of big brown bats (Eptesicus fuscus) are not necessarily correlated with socially oriented behaviors [40][41][42]. These previous studies confirmed that bats have distinct personality traits, but the relationships between personality and body size remain unclear.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The Spix's disc-winged bat (Thyroptera tricolor) within social groups exhibits consistent individual differences in vocal behavior [38,39]. The isolated behaviors of big brown bats (Eptesicus fuscus) are not necessarily correlated with socially oriented behaviors [40][41][42]. These previous studies confirmed that bats have distinct personality traits, but the relationships between personality and body size remain unclear.…”
Section: Introductionmentioning
confidence: 84%
“…It is common to measure aggression in terms of frequency or proportion. For example, in studies of big brown bats (E. fuscus), the frequency of biting was used as a measure of aggression [40]. The aggressiveness of Wildtype Groningen rats (Rattus norvegicus) was measured by the proportion of the time spent on aggression to the total experimental time [30].…”
Section: Personality Traits Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Parasite risk is thought to be a major cost of social behaviour (Alexander, 1974;Altizer et al, 2003) and sociability is a trait with potentially important implications for parasite transmission. Despite the relatively solitary nature of adult male bats, they are still more gregarious than many other mammalian species (Thomas et al, 1979) and we recommend that future studies quantify individual differences in sociability among demographics and individual bats to assess its importance for transmission (e.g., Kilgour & Brigham, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of fission-fusion in bat societies suggests that preferential relationships are complex and may be explained by motivations other than simple kinship (Gillam et al 2011;Metheny et al 2008;Patriquin et al 2010;Kilgour and Brigham 2013). For example, females big brown bats are highly philopatric and live in colonies with overlapping matrilines (Vonhof et al 2008).…”
Section: Introductionmentioning
confidence: 99%